Impact of Chronic Ethanol and Cannabis Intake on Reproductive Hormones and Associated Histopathological Changes in Adult Albino Rats - El-sayed Gawesh; Ahmed Elshoura; Khaled Elhamaky; Ahmed Mostafa; Mustafa Al-Qulaly; Ahmed El-Assal (International Journal of Medical Arts, 2023)
Background: Cannabis is a versatile plant in conventional medicine, and intera-peritoneal infusion of its hydroalcoholic extract reduced sperm motility substantially over time. Seminiferous tubule diameter and sperm count both significantly reduced when as opposed to the control group. The reproductive system of animals undergoes morphological and physiological alterations as a result of chronic ethanol intake. Vitamin C has a crucial part in the male reproductive system and plays an antioxidant role in organisms by scavenging reactive oxygen species [ROS] created by oxidizing agents.Aim of the work: Evaluation of effects of ethanol and cannabis consumption on adult albinos' reproductive hormones together with histopathological changes.Patients and Methods: The forty animals were divided into four groups: group I, which received only normal saline; group II, which was given oral ethanol [30% [v/v]] at a dose of 2 g/kg; group III, which obtained oral cannabis at an amount of 1.5 mg/kg; and group IV, which acquired ethanol and cannabis by way of ingestion and at the dose indicated above for 28 days. 24 hours after the last dose had been administered, rats were killed, blood was taken, and the resulting serum chemical profile was evaluated. Testes were gathered and measured. Glutathione, catalase, superoxide dismutase peroxidase inhibitor glutathione, malondialdehyde, and histology [hematoxylin and eosin] levels in the testis were measured.Results: In comparison to controls, all experimental groups had significantly lower testosterone levels and testicular glutathione, catalase, superoxide dismutase [SOD], and peroxidase glutathione levels. Malondialdehyde, on the other hand, was markedly elevated in each group of experiments as compared to controls. Alcohol and/or cannabis produced structural abnormalities in the testicles.Conclusion: Ethanol and cannabis abuse had comparable, additive, and synergistic effects that were detrimental to male reproductive health. These effects may be related to how they damaged the body's antioxidant protection mechanism.